Physicochemical, Functional, Microbial, and Sensory Characteristics of Precooked Complementary Flour Produced from Yellow Maize Enriched with Roasted Cashew Almonds and Baobab Pulp - Wilfred Ngaha Damndja; Aurelie Solange Agume Ntso; Thérèse Josiane Ngatchic Metsagang; Hermionne Djello Nkali (Journal of Food Quality)
The aim of his study was to formulate and characterize precooked complementary flours based on yellow maize, cashews, and baobab pulp. To achieve this goal, yellow maize was malted and cooked and cashew almonds were roasted and cooked, while baobab pulp did not undergo any treatment. Indeed 3 materials were used: yellow maize, cashew almonds, and baobab pulp. All the food materials were dried and ground into flours. Four different complementary flours, MCB1 (73/23/4), MCB2 (72.5/25/2.5), MCB3 (75/22.5/2.5), and MCB4 (74/24/2), were formulated by blending yellow maize flour with cashew, almond, and baobab pulp flours. The proximate composition (moisture content, total ash, total carbohydrate, crude protein, crude fat, and crude fiber), soluble sugar, some minerals (iron and calcium) and vitamins (A and C), the functional properties (water absorption capacity (WAC) and water solubility index (WSI)), and the microbial characteristics of formulated flours were determined. Gruels were prepared from these flours, and their physical and sensory properties, as well as energy density, were determined. The results showed that for all the flours formulated, macronutrients, vitamins, and energy values were in the range recommended by the World Food Program. But concerning minerals, iron (5.12–5.30 mg/100 g DM) and calcium (141.02–181.94 mg/100 g DM) contents were lower compared to the norm. All the flours produced had good WAC, with the highest values for MCB3 (425.46%) and MCB4 (427.25%). The WSI of the formulated flours had the same trend as WAC. The flours presented good microbial characteristics, with no harmful microorganisms. The gruels prepared with the formulated flours exhibited a viscosity between 2497 and 2654 mPa.s, which indicates that they could be easily swallowed by young children with good energy density. The gruels were also accepted by the consumers, with the highest score of overall acceptability for the one prepared with MCB1. Based on their demonstrated nutritional values and functional properties, the flours formulated are potential complementary food for feeding young children but need to be fortified with minerals.